Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1007/s00417-006-0360-0
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of topically applied levofloxacin 0.5% and ofloxacin 0.3% into the vitreous of the non-inflamed human eye

Abstract: Equal dosing with topical administration of levofloxacin 0.5% and ofloxacin 0.3% allows better penetration into the vitreous for levofloxacin, but the levels of mean concentrations of each drug did not exceed the MIC(90) or MIC(50) for most ocular pathogenic bacteria in terms of conventional endophthalmitis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
(31 reference statements)
0
15
0
1
Order By: Relevance
“…11 This purified mixture is more water soluble than ofloxacin at neutral pH, 11 allowing it to be formulated at a higher concentration than ofloxacin or ciprofloxacin. This in turn produces higher ocular tissue concentrations, [12][13][14] creating a theoretical improvement in clinical efficacy and an established reduction in the risk of selecting for fluoroquinolone resistance. 15 Levofloxacin also demonstrates increased activity against Streptococci relative to second-generation fluoroquinolones.…”
Section: Introductionmentioning
confidence: 98%
“…11 This purified mixture is more water soluble than ofloxacin at neutral pH, 11 allowing it to be formulated at a higher concentration than ofloxacin or ciprofloxacin. This in turn produces higher ocular tissue concentrations, [12][13][14] creating a theoretical improvement in clinical efficacy and an established reduction in the risk of selecting for fluoroquinolone resistance. 15 Levofloxacin also demonstrates increased activity against Streptococci relative to second-generation fluoroquinolones.…”
Section: Introductionmentioning
confidence: 98%
“…In the absence of consent for more-aggressive therapy, we chose levofloxacin, a third-generation fluoroquinolone. Although it has good vitreous penetration, the concentrations achieved were well under the minimal inhibitory concentration (MIC) for most ocular pathogenic bacteria in endophthalmitis [5]. Studies, however, suggested that, once the P. aeruginosa infection had involved the subretinal space, visual prognosis is poor, with four out of five cases required enucleation despite aggressive surgical and medical intervention [4].…”
Section: Discussionmentioning
confidence: 98%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Levofloxacin shows pH-dependent solubility. Over the pH range of 2-5, the solubility is essentially constant, approximately 200 mg/mL; above pH 5.5, the solubility increases to a maximum value of approximately 300 mg/mL at about pH 6.5, whereas above pH 6.5, the solubility decreases and reaches its minimum value of approximately 30 mg/mL at about pH 7.5.…”
Section: Chemical Properties Solubilitymentioning
confidence: 99%